2011
DOI: 10.1103/physrevlett.106.148102
|View full text |Cite
|
Sign up to set email alerts
|

Curvature-Dependent Elastic Properties of Liquid-Ordered Domains Result in Inverted Domain Sorting on Uniaxially Compressed Vesicles

Abstract: Recent tumor growth models are often based on the multiphase mixture framework. Using bifurcation theory techniques, we show that such models can give contour instabilities. Restricting to a simplified but realistic version of such models, with an elastic cell-to-cell interaction and a growth rate dependent on diffusing nutrients, we prove that the tumor cell concentration at the border acts as a control parameter inducing a bifurcation with loss of the circular symmetry. We show that the finite wavelength at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…6G, H (Table S1), suggests that significant structural changes to lipid bilayers are not responsible for the antimicrobial action of PMB1, but rather that modifications to the diffusive properties of these lipids disrupts Gram-negative membranes. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 window that corresponds to the minimum of the PMF profile calculated at 310 K (see 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 drastically alter the physical properties of bilayers including elastic moduli, shape, mechanical stress and tension, [53]…”
Section: Simulations Of Pmb1 Peptides With Lps Bilayersmentioning
confidence: 99%
“…6G, H (Table S1), suggests that significant structural changes to lipid bilayers are not responsible for the antimicrobial action of PMB1, but rather that modifications to the diffusive properties of these lipids disrupts Gram-negative membranes. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 window that corresponds to the minimum of the PMF profile calculated at 310 K (see 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 drastically alter the physical properties of bilayers including elastic moduli, shape, mechanical stress and tension, [53]…”
Section: Simulations Of Pmb1 Peptides With Lps Bilayersmentioning
confidence: 99%
“…We applied a parameterized model of cholesterol that has been shown to capture the liquid disorder to liquid order (lipid rafts) phase transition (39). With this simulation model, we have previously demonstrated the enhanced affinity of both PE lipids and cholesterol for the inner and thus negatively curved monolayer of a 20-nm-sized vesicle (34,40).…”
Section: Significancementioning
confidence: 99%
“…Moreover, despite the widespread use of CH models for highly curved structures (e.g., an hourglass-shaped fusion stalk) [22,23], it is unclear whether or not the harmonic approximation of constant κ is sufficiently accurate in this regime. The first simulations to test this approximation at higher curvatures [6,24] used heavily coarse-grained lipid models, with conflicting results; however, two recent studies have reported anharmonic behavior for binary [25] and ternary (raft-forming) lipid mixtures [26]. We therefore apply our proposed method to compute bending free energies and κ up to very high curvatures to rigorously test the range of validity of the harmonic approximation.…”
mentioning
confidence: 99%
“…This nonlinearity is accounted for by adding a quartic bending term ðμ=4ÞH 4 to the integrand of (2) [6,26,[35][36][37] and integrating to obtain a sum of quadratic and quartic energy terms,…”
mentioning
confidence: 99%
See 1 more Smart Citation